If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 10) = (5x + -5) Reorder the terms: (10 + 2x) = (5x + -5) Remove parenthesis around (10 + 2x) 10 + 2x = (5x + -5) Reorder the terms: 10 + 2x = (-5 + 5x) Remove parenthesis around (-5 + 5x) 10 + 2x = -5 + 5x Solving 10 + 2x = -5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 10 + 2x + -5x = -5 + 5x + -5x Combine like terms: 2x + -5x = -3x 10 + -3x = -5 + 5x + -5x Combine like terms: 5x + -5x = 0 10 + -3x = -5 + 0 10 + -3x = -5 Add '-10' to each side of the equation. 10 + -10 + -3x = -5 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = -5 + -10 -3x = -5 + -10 Combine like terms: -5 + -10 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| -2r=100 | | -2(b+4)+5(5-4b)=61 | | 6(4+t)-4(t+3)= | | -5(r+8)=-78 | | Sin(180-x)=-sinx | | -2(b+4)+5(5-4b)=-61 | | 22=7x+6-3x | | 2n-28=-32+4n | | 3r+5=0 | | 10h-22=48 | | 188.9024=2*3.14*3.2*3.2+2*3.14*3.2*h | | 3(1-5m)-(1+7m)=68 | | 15x+20x=7 | | 41+27= | | 3r-y=0 | | 3.3+10m=7.19 | | 2(x+4)-5(x-3)=18 | | 3=-y+6 | | t*5-4=14 | | 88m^2=3+w | | -6(-3x+6)=90 | | x-2(2x-5)=8 | | 37.50-0.5x=42.75-0.75x | | 15x^2+20x-20=0 | | -109=3-4(8n+4) | | x+82+x+102=180 | | log[2](5x+6)=5 | | 7(t-3)+8t=5(3t+4)-11 | | d+20+0.2d= | | t(x)=11x-725 | | (2x-3)squared=5 | | 5+2x=234234325.00302030303030303030101010324234 |